Task-shifting in dementia care: a comparative analysis of consultation models and proposed collaborative ecosystem in Japan - Ito, Kae; Okamura, Tsuyoshi (Frontiers in Psychiatry, 2025)
IntroductionWith an aging population, task-shifting in dementia care has been proposed to meet the needs of persons living with dementia (PLWD). In Japan, the Initial-phase Intensive Support Service (IPIS), led by primary care physicians, was introduced alongside traditional Psychogeriatric Services (PS), which are psychiatrist-led. However, the impact of this shift on care capacity remains unclear.MethodsThis study employed a convergent mixed-methods design to examine two dementia outreach services in Tokyo: PS and IPIS. This study aimed to: 1) compare the content of consultations between PS and IPIS; 2) identify tasks that could not be shifted; and 3) propose a collaborative care model to address identified service gaps. We analyzed 121 PS cases and 213 IPIS case records, and conducted interviews with team members to explore cases where IPIS was perceived as less equipped.ResultsThe IPIS Service was generally suitable for early-stage dementia without severe behavioral symptoms but less equipped to manage: 1) mental health conditions beyond dementia; 2) long-standing psychosocial issues; and 3) acute crises—areas where PS traditionally intervened.DiscussionThe findings highlight the need for strengthened collaboration between primary care and psychiatric services. We propose a collaborative care ecosystem in which primary care physicians lead community-based dementia care, supported by psychogeriatric consultation.